Localization of fugitive methane emission from natural gas distribution network of Titas Gas - Mandal, P.C. (De Gruyter Open Ltd, 2017)
The aim of this paper is to localize the fugitive leaks from the above ground facilities of the existing system of Titas Gas (TG) after developing mathematical model for fugitive emission. Soap screening techniques and Gasurveyor 500 series instrument were used in this study for detecting potential leaks. Leaked gas was quantified using either Hi-Flow gas sampler or bagging measurements system. The results show that the respective potential gas leaking point of City Gate Station (CGS), commercial Regulating and Metering Station (RMS), industrial RMS, residential RMS and Town Bordering Station (TBS)/District Regulating Station (DRS) are scrubber dump valve (average leak rate 217.00 L/min), insulating point (average leak rate 4.04 L/min), tube fitting connector (average leak rate 8.00 L/min), connector (average leak rate 1.55 L/min) and pressure relief valve (average leak rate 437.92 L/min). Fugitive methane emission can be reduced by stopping leaks of fittings or components having high KLeak value. © by Pradip C. Mandal 2017.